Concurrent training for sports performance: The two sides of the medal - Berryman, N.; Mujika, I.; Bosquet, L. (International Journal of Sports Physiology and Performance, 2018)
The classical work by Robert C. Hickson showed in 1980 that the addition of a resistance training protocol to a predominantly aerobic program could lead to impaired leg strength adaptations in comparison to a resistance-only training regimen. This interference phenomenon was later highlighted in many reports, including a meta-analysis. However, it seems that the interference effect has not been consistently reported, probably because of the complex interactions between training variables and methodological issues. On the other side of the medal, Dr Hickson and colleagues subsequently (1986) reported that a strength training mesocycle could be beneficial for endurance performance in running and cycling. In recent meta-analyses and review articles, it was demonstrated that such a training strategy could improve middle- and long-distance performance in many disciplines (running, cycling, cross-country skiing and swimming). Interestingly, it appears that improvements in the energy cost of locomotion could be associated with these performance enhancements. Despite these benefits, it was also reported that strength training could represent a detrimental stimulus for endurance performance if an inappropriate training plan has been prepared. Taken together, these observations suggest that coaches and athletes should be careful when concurrent training seems imperative in order to meet the complex physiological requirements of their sport. Therefore, this brief review will present a practical appraisal of concurrent training for sports performance. In addition, recommendations will be provided so that practitioners could adapt their interventions based on the training objectives. Abstract from author